Medical vocation in medical students of a Peruvian university - Perales, Alberto (2014)
Objectives: To determine perceptions and development of medical vocation in undergraduate students of a Peruvian University School of Medicine. Design: Qualitative study. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos. Participants: Medical students. Methods: Semi-structured interviews were applied to 50 medical students from first through fifth year, inquiring on: 1) Definition of vocation, 2) Definition of medical vocation, and 3) Student’s vocational development. Main outcome measures: Comparison of medical vocation between current students and graduate phsysicians. Results: Half of the students were female, with mean age 21.7 years. Eight per cent were sons of physicians; 82% were born in Lima city. The students identified three characteristics in medical vocation: wish to help, will to serve, and disposition for sacrifice. In relation to his/her own vocational development, the decision to study medicine may begin at an early age or in adolescence, and even be emerging at the time of enrollment to the School of Medicine. Vocation is also influenced by diverse personal experiences mainly contact with physician’s relatives or with physicians while suffering personal illness. There are also family influence and search for social prestige. Conclusions: Comparatively, medical vocation in undergraduate students and graduate physicians show similarities and differences. The expectation to be an altruistic physician with spiritual, economic and social motivations were common to both groups. Among the differences, the students showed a more external motivation to begin the career of medicine and fascination for technologic development. Some recommendations are given to teaching centers.